Oral dydrogesterone versus oral micronized progesterone in threatened miscarriage: protocol paper for a randomized controlled trial - Alka Kriplani; Gouri Shankar Kamilya; T Ramani Devi; Ashima Taneja; Amol Pawar; Gayathri Karthik Nagesh; Tapan Pattanaik; Tanusree Gupta; Mahima Jain; Monjori Mitra (Reproduction and Fertility)
Threatened miscarriage is a common complication of early pregnancy characterized by symptoms of vaginal bleeding with/without abdominal cramps/pain in the first trimester. Progestogens are often administered for the management of this condition. Presented herein is the protocol of an ongoing, multicentric clinical trial to investigate the efficacy and safety of micronized progesterone (natural progestogen) compared to dydrogesterone (synthetic isomer of progesterone). A total of 304 eligible pregnant women aged 20–39 years, diagnosed with threatened miscarriage, will be enrolled during 5–12 weeks of gestation and randomized equally to receive either oral dydrogesterone (40 mg stat, followed by 10 mg three times a day) or oral micronized progesterone (200 mg two times a day) up to one week after stoppage of bleeding or if bleeding does not stop, then treatment will be continued till a maximum of 14 weeks of gestation (unless miscarriage is confirmed earlier or the investigator decides to prolong treatment for better outcome or if bleeding relapses). Scheduled visits after enrollment will be conducted during 6–13, 8–14, 18–20 and 24–26 weeks of gestation, in addition to a visit at the end of treatment at 14 weeks and another after parturition. The primary endpoint of the study is the miscarriage rate before 20 weeks of gestation. Secondary endpoints include the ongoing pregnancy rate at 24 weeks, treatment-induced changes in serum levels of cytokines and time to symptom resolution. Apart from the incidence of treatment-emergent adverse events, safety endpoints include changes in complete blood count and the results of liver and kidney function tests from baseline to 14 and 24–26 weeks of gestation. Delivery outcomes are exploratory endpoints of the study.